IDNLearn.com offers a reliable platform for finding accurate and timely answers. Join our community to receive prompt and reliable responses to your questions from knowledgeable professionals.

20 POINTS !!

x^2+y^2+2x+2y=0

x^2+y^2+2x+6y+9=0 solve each system using substitution

Will mark brainlyest if steps are provided


Sagot :

Answer:

Step-by-step explanation:

x²+y²+2x+2y=0  ...(1)

x²+y²+2x+6y+9=0  ...(2)

subtract (1) from (2)

x²+y²+2x+6y+9-(x²+y²+2x+2y)=0

x²+y²+2x+6y+9-x²-y²-2x-2y=0

4y+9=0

4y=-9

[tex]y=-\frac{9}{4}[/tex]

put in (1)

[tex]x^{2} +(-\frac{9}{4} )^2+2x+2(-\frac{9}{4} )=0\\x^{2} +2x+\frac{81}{16} -\frac{9}{2} =0\\x^{2} +2x+\frac{81-72}{16} =0\\x^{2} +2x=-\frac{9}{16} \\adding 1 \\x^{2} +2x+1=-\frac{9}{16} +1\\(x+1)^2=\frac{-9+16}{16} \\x+1=\pm\sqrt{\frac{7}{16} } \\x=-1 \pm\frac{\sqrt{7} }{4} \\x=\frac{\sqrt{7} -4}{4} \\and\\x=\frac{-\sqrt{7} -4}{4}[/tex]

solution is ((√7-4)/4,-9/4)

and ((-√7-4)/4,-9/4)